Aspek Hukum Bisnis Lembaga Perkreditan Desa (LPD) Dalam Pemberdayaan Desa Adat di Bali - I Wayan Suarjana (Jurnal Preferensi Hukum, 2025)
Village Credit Institution (Lembaga Perkreditan Desa/LPD) in Bali represents a unique legal entity within Indonesia's financial system, combining positive law principles with local wisdom values. LPD operates as a microfinance institution within traditional village scope by implementing dual legal systems that create juridical complexity in its operations. This research aims to analyze the juridical construction of LPD business law aspects in traditional village empowerment context, evaluate vertical and horizontal synchronization of LPD regulations, examine juridical implications of LPD's legal status as sui generis legal entity, and analyze the effectiveness of legal norms in supporting LPD's role as traditional village empowerment instrument. The study employs normative juridical methods with statutory, conceptual, and case approaches. LPD's status as sui generis legal entity creates complexity in implementing dual legal systems while providing flexibility to accommodate traditional values. There are 1,433 LPDs with total assets of IDR 28.7 trillion that have contributed IDR 1.2 trillion to traditional village development during 2019-2023. Vertical synchronization shows adequate consistency, while horizontal synchronization still faces harmonization challenges. Dispute resolution rate through customary mechanisms reaches 94% with average time of 21 days. LPD's legal construction creates an innovative model providing flexibility to accommodate local wisdom values while creating legal certainty complexity. LPD legal norm effectiveness is reflected in real contributions to traditional village empowerment through mandatory profit allocation mechanisms and implementation of corporate social responsibility based on tri hita karana.